You're welcome, universe - Gardner, Whitney (Alfred A Knopf, 2017)
When Julia gets kicked out of the Kingston School for the Deaf for putting up an illegal mural, she is moved to a mainstream school in the suburbs where she starts putting up more art, but she soon finds that someone is showing off their skills by addingto her tags.